AUDIT COMMITTEE EFFECTIVENESS AND SUSTAINABILITY DISCLOSURE OF FTSE4GOOD BURSA MALAYSIA INDEXED COMPANIES - Iskandar Zulkarnaen Muhamad Amin; Norfadzilah Rashid; Ridzwana Mohd Said; Aimi Abdul Wahab (International Journal of Accounting, Finance and Business, 2020)
This study examines the relationship between the audit committee’s attributes and sustainability disclosure of companies listed in FTSE4Good Bursa Malaysia Index (FTSE4G). The index consists of top 200 Malaysian stocks in the FTSE Bursa Malaysia EMAS Index, screened in accordance with the transparent and defined environmental, social and governance criteria, that designed to identify Malaysian companies with recognised corporate responsibility practices. Using the resource dependency theory, the study provides empirical evidence on the significant contributions of audit committee’s 1) independence, 2) gender diversity, and 3) diligence, towards the level of sustainability disclosure in eighteen (18) FTSE4G companies. The results reveal that audit committee’s independence and diligence have significant and positive impact on the level of sustainability disclosure, while audit committee’s gender diversity, has no impact. Insights gained from the study are useful for industrial practitioners and scholars of related fields.